A terephthalic acid hydrogenation catalyst and its preparation method and application

By developing a combination of Ni-based catalysts and porous structural carriers, the existing terephthalic acid hydrogenation catalysts have solved the problems of large amounts of precious metals, high costs and limited active sites, achieving efficient 4-CBA conversion and economical catalysts. sexual production.

CN119175113BActive Publication Date: 2025-01-21LINQU HENGHUI NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411649341.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-21
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The existing terephthalic acid hydrogenation catalysts have problems such as high usage, high cost, poor dispersion and low utilization rate of noble metal palladium, and the support active sites are limited, which affects the catalytic effect.

Method used

Develop a terephthalic acid hydrogenation catalyst based on Ni-based catalyst, and prepare a catalyst carrier with a porous structure through heat treatment and ultrasound of nanometer ytterbium oxide, potassium hydrogen oxalate, acridone acetic acid and polyaryl ether nitrile. , and enhance the activity and stability of the catalyst through the coordination reaction of 4-(tert-butyldimethylsiloxy)phenylboronic acid and nickel-copper-iron-magnesium powder.

Benefits of technology

The conversion rate of 4-CBA is improved, the production cost of the catalyst is reduced, the high temperature and high pressure resistance activity and structural stability of the catalyst are enhanced, the preparation process is simplified, and the complexity and cost are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119175113B_ABST
    Figure CN119175113B_ABST
Patent Text Reader

Abstract

The present invention provides a terephthalic acid hydrogenation catalyst and its preparation method and application, belongs to the field of catalyst technology, by steps: S1, after mixing nano ytterbium oxide, potassium hydrogen oxalate, acridone acetic acid and polyarylether nitrile, heat treatment, cooling, ultrasound, washing, drying, obtain a catalyst carrier with a porous structure; S2, 4-(tert-butyldimethylsilyloxy)phenylboric acid is added to ethanol, and after stirring, pre-treated nickel copper iron magnesium powder is added for homogenization, heating and stirring, cooling, centrifugation, washing, drying, and catalyst powder is obtained; S3, the suspension of the catalyst powder is added to the suspension of the catalyst carrier, heating and stirring, cooling, centrifugation, washing, heat treatment, and terephthalic acid hydrogenation catalyst is obtained. The catalyst of the present invention can not only achieve excellent hydrogenation catalytic effect, but also has certain cost-effectiveness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a terephthalic acid hydrogenation catalyst and a preparation method and application thereof. Background Art

[0002] In modern industrial production, the preparation of PTA (terephthalic acid) is usually carried out by liquid-phase oxidation of para-xylene to generate CTA (crude terephthalic acid) containing more impurities, and then the CTA is hydrogenated to obtain PTA with higher purity. The hydrogenation of CTA is mainly to remove 4-CBA (para-carboxybenzaldehyde), because 4-CBA is a key impurity in the production process of PTA, and its presence will affect the quality and color of PTA, thereby affecting the performance of the final polyester product. The hydrogenation of CTA is mainly based on precious metal catalysts such as palladium carbon. Under high temperature and high pressure, the 4-CBA in CTA is reduced to p-toluic acid (PT acid) with better water solubility, thereby obtaining PTA with higher purity.

[0003] Although the catalytic activity and structural stability of precious metal catalysts such as palladium carbon under high temperature and high pressure conditions are better than those of non-precious metal catalysts, the sources of these precious metals mainly rely on imports, the cost is too high, and the precious metal palladium in the catalyst has poor dispersion and low utilization rate, which in turn has a certain impact on the catalytic activity. The catalyst needs to be added or replaced regularly, and it is difficult to obtain a high 4-CBA conversion rate.

[0004] The Chinese patent application document with publication number CN112239404A and titled Hydrofining Reaction and Catalyst thereof discloses a method for preparing a hydrofining catalyst and a catalyst thereof. The method for preparing a hydrofining catalyst comprises the following steps: subjecting a mixture including a palladium source, a zinc source, a solvent, an activated carbon carrier and a solvent to heat treatment and reduction treatment. The hydrofining reaction catalyst of the invention has a conversion rate of up to 99.2% for p-carboxybenzaldehyde under industrial reaction conditions, effectively improving the utilization rate of precious metal palladium, reducing the production cost of precious metal catalysts, and having better stability.

[0005] However, the catalyst prepared by this invention still has the following technical defects. First, although this invention reduces the amount of palladium used by introducing zinc, palladium is still a precious metal with a high price. Even if the amount used is reduced, the cost is still high during long-term large-scale production. Secondly, the carrier used in this invention is coconut shell-based activated carbon. Although this material has a high specific surface area and good thermal stability, its surface active sites are relatively limited and it does not have catalytic activity, which will have a certain impact on the hydrogenation catalytic effect of the catalyst. Although the catalytic activity and stability of the catalyst can be improved by introducing an excess of organic amines, organic amines have poor thermal stability and are easily decomposed or volatilized at high temperatures, which may affect the selectivity and efficiency of the catalytic reaction.

[0006] Therefore, it is necessary to provide a terephthalic acid hydrogenation catalyst and a preparation method and application thereof to solve the problems existing in the above-mentioned prior art. Summary of the invention

[0007] In view of this, the present invention provides a terephthalic acid hydrogenation catalyst and a preparation method and application thereof, and develops an efficient Ni-based catalyst to have excellent high temperature and high pressure catalytic activity and structural stability, thereby improving the conversion rate of 4-CBA and ensuring the economic benefits of the production process.

[0008] To achieve the above object, the present invention provides a method for preparing a terephthalic acid hydrogenation catalyst, comprising the following steps:

[0009] S1, mixing nano-ytterbium oxide, potassium hydrogen oxalate, acridone acetic acid and poly(arylene ether nitrile) to obtain a mixed suspension, then heat-treating, cooling, ultrasonicating and washing, and heat-treating, cooling, ultrasonicating and washing again, and after drying and cooling, obtaining a catalyst carrier with a porous structure;

[0010] S2, adding 4-(tert-butyldimethylsilyloxy)phenylboric acid to ethanol, stirring, adding pretreated nickel, copper, iron and magnesium powders, homogenizing, heating and stirring, cooling, centrifuging, washing and drying to obtain catalyst powder;

[0011] S3. Add the suspension of catalyst powder into the suspension of catalyst carrier, and heat, stir, centrifuge, wash, heat treat and cool to obtain terephthalic acid hydrogenation catalyst.

[0012] The preparation steps of the catalyst carrier in the present invention are simplified, and there is no need to add multiple components such as pore-forming agent, foaming agent and cross-linking agent, which greatly reduces the complexity and preparation cost of the preparation process. The potassium hydrogen oxalate used in the present invention can not only partially dissociate in N, N-dimethylformamide solution to form hydrogen ions and oxalate ions, and complex with existing metal ions on the surface of nano-ytterbium oxide, enhance the interaction between nanoparticles, and improve the dispersibility of nano-ytterbium oxide in solution, but also can be thermally decomposed to generate gas and form a pore structure when heat-treated in a hot air circulation oven with a gas discharge port at 220°C, 240°C and 260°C. The acridone acetic acid and polyarylether nitrile added subsequently contain multiple polar groups such as carboxyl and amino groups, and the partial dissociation of potassium hydrogen oxalate in the reaction system provides a certain acidic environment, which is conducive to the formation of hydrogen bonds and other interactions between these polar groups, and these hydrogen bonds can be used as cross-linking points to connect potassium hydrogen oxalate, acridone acetic acid and polyarylether nitrile, and promote the formation of a mixed suspension system. Among them, the aromatic ring in acridone acetic acid and the aromatic structure of polyarylether nitrile will also have π-π interaction, which helps to further promote the formation of the mixed suspension system, and promotes the interaction between the components with the nano-ytterbium oxide and potassium hydrogen oxalate in the solution under mechanical stirring and heat treatment steps, thereby forming a catalyst carrier with a porous structure. Among them, the addition of nano-ytterbium oxide can provide additional active sites, which is convenient for the introduction of subsequent catalyst active components.

[0013] This scheme also enhances the dispersion of nickel-copper-iron-magnesium powder by the coordination and hydrogen bonding of polar groups such as siloxy of 4-(tert-butyldimethylsiloxy)phenylboronic acid with existing metal atoms and other active ingredients on the surface of nickel-copper-iron-magnesium powder, and the introduced phenyl, tert-butyl, siloxy groups, etc. can also increase the active sites and thermal stability of the catalyst powder. Among them, tert-butyl and dimethyl are hydrophobic groups, which help to improve hydrophobicity, and the steric hindrance of tert-butyl is large, which can prevent other larger or highly polar molecules (benzene ring, carboxyl, etc.) from approaching the catalyst surface, reducing unnecessary adsorption. Then, the polar groups such as tert-butyl and siloxy groups on the catalyst powder form hydrogen bonds and other interactions with polar groups such as amino groups of the catalyst carrier with a porous structure, thereby enhancing the binding force between the catalyst powder and the catalyst carrier, and making the structure more compact through heat treatment.

[0014] Optionally, in step S1, nano-ytterbium oxide and potassium hydrogen oxalate are added to N,N-dimethylformamide, homogenized at 600-700 r / min for 20-30 min, acridone acetic acid is added, stirred at 400-500 r / min for 1-2 h, and then polyarylether nitrile is added, stirred at 400-500 r / min for 1-2 h to obtain a mixed suspension.

[0015] Optionally, in step S1, the catalyst carrier with a porous structure is heat-treated by a mixed suspension in a hot air circulation oven containing a gas exhaust port at 150°C and 170°C for 10 to 12 hours, respectively, and after cooling to room temperature, ultrasonically treated at a rotation speed of 400 to 500 r / min for 10 to 15 minutes, and washed, and then heat-treated again in a hot air circulation oven containing a gas exhaust port at 220°C, 240°C and 260°C for 3 to 4 hours, respectively, after cooling to room temperature, ultrasonically treated at a rotation speed of 400 to 500 r / min for 10 to 15 minutes, and washed, dried at 80 to 90°C for 8 to 10 hours, and cooled to room temperature to obtain.

[0016] The heat treatment temperature used in the present invention is different, and a temperature gradient can be formed, which helps to improve the thermal stability of the material, and high temperature also helps to improve the reactivity of the group, thereby forming a more compact structure. Secondly, the heat treatment process at 220°C, 240°C and 260°C not only helps to further remove the N,N-dimethylformamide solution, but also causes potassium hydrogen oxalate to decompose and generate gas, forming pores, and increasing the specific surface area of ​​the catalyst carrier.

[0017] Optionally, in step S2, the pretreated nickel-copper-iron-magnesium powder is obtained by ultrasonicating the nickel-copper-iron-magnesium powder in anhydrous ethanol at a speed of 400-500 r / min for 10-20 min, centrifuging at 6000-7000 rpm for 10-15 min, drying the precipitate at 80-90° C. for 2-3 h, and cooling to room temperature.

[0018] Optionally, in step S2, 4-(tert-butyldimethylsilyloxy)phenylboric acid is added to ethanol, stirred at a speed of 400-500 r / min for 20-30 min, and then the pretreated nickel-copper-iron-magnesium powder is added, homogenized at a speed of 400-500 r / min for 30-40 min, and then stirred at a speed of 300-400 r / min for 2-3 h at 70-80 ° C., cooled to room temperature, centrifuged at 6000-7000 rpm for 10-15 min, washed, dried in a hot air oven at 100-110 ° C. for 2-3 h, and cooled to room temperature to obtain a catalyst powder.

[0019] The pretreatment step of the present invention removes pollutants on the surface of nickel-copper-iron-magnesium powder by ultrasound and heating and drying, thereby enhancing the dispersibility of the powder. Secondly, controlling the reaction temperature and stirring rate helps to optimize the synthesis process of the catalyst and improve its stability and reaction performance. In addition, by removing residues through centrifugation and washing, the purity of the catalyst is improved and the catalytic effect is optimized.

[0020] Optionally, in step S2, the mass ratio of the pretreated nickel-copper-iron-magnesium powder to 4-(tert-butyldimethylsilyloxy)phenylboric acid is 20:3.

[0021] When the mass ratio of nickel-copper-iron-magnesium powder to 4-(tert-butyldimethylsilyloxy)phenylboric acid used in the present invention is 20:3, the prepared terephthalic acid hydrogenation catalyst has good performance in hydrogenation catalysis of 4-CBA.

[0022] Optionally, in step S3, the suspension of catalyst powder is obtained by homogenizing the catalyst powder in ethanol at 400-500 r / min for 20-30 min; the suspension of catalyst carrier is obtained by homogenizing the catalyst carrier in ethanol at 400-500 r / min for 20-30 min.

[0023] Optionally, in the step S3, the preparation of the terephthalic acid hydrogenation catalyst is carried out by adding a suspension of the catalyst powder to a suspension of the catalyst carrier at a stirring speed of 400 r / min and a dropping speed of 2 mL / min, and after the dropwise addition is completed, stirring the reaction is continued at 60-70°C for 3-4 hours, and after cooling to room temperature, centrifuging at 6000-7000 rpm for 10-15 minutes, washing, and then heat-treating in a hot air oven at 150°C, 200°C and 250°C for 2-3 hours respectively, and cooling to room temperature to obtain.

[0024] The homogenization step in the present invention helps to disperse the catalyst powder and the catalyst carrier in ethanol to form a suspension. Subsequently, mixing and reacting at a suitable temperature and stirring rate helps to promote uniform distribution and good bonding of the catalyst. At the same time, unreacted residues and impurities are removed through multiple washings, and then heat treatment is performed to improve the thermal stability of the catalyst.

[0025] In order to achieve the above-mentioned object, the present invention also provides a terephthalic acid hydrogenation catalyst, comprising the following raw materials in parts by weight: 10-12 parts of nano ytterbium oxide, 25-30 parts of acridone acetic acid, 5-6 parts of potassium hydrogen oxalate, 8-10 parts of polyarylether nitrile, 20-25 parts of nickel copper iron magnesium powder, 3-3.5 parts of 4-(tert-butyldimethylsilyloxy)phenylboric acid, and 40-50 parts of N,N-dimethylformamide.

[0026] The present invention also provides an application of a terephthalic acid hydrogenation catalyst, such as being used for catalytic hydrogenation reaction of p-carboxybenzaldehyde contained in crude terephthalic acid to generate p-toluic acid.

[0027] The above technical solution of the present invention includes at least the following beneficial effects:

[0028] 1. The potassium hydrogen oxalate used in the present invention can not only dissociate to form hydrogen ions and oxalate ions, and complex with metal ions on the surface of nano-ytterbium oxide to improve the dispersibility of nanoparticles, but also decompose to produce gas during heat treatment at 220°C, 240°C and 260°C to form a porous structure, and the subsequently added acridone acetic acid and polyarylether nitrile are connected by polar groups through hydrogen bonds and other interactions under a certain acidic environment, which promotes the formation of a mixed suspension system, and then forms a catalyst carrier with a porous structure. Among them, the addition of nano-ytterbium oxide provides additional active sites for the subsequent introduction of catalyst active ingredients.

[0029] 2. Preparation of the catalyst powder of the present invention The siloxy groups of 4-(tert-butyldimethylsiloxy)phenylboronic acid interact with the active groups on the surface of nickel-copper-iron-magnesium powder through coordination and hydrogen bonding, which effectively enhances the dispersibility of the catalyst powder. Among them, the introduced phenyl, tert-butyl and siloxy groups not only increase the active sites, hydrophobicity and thermal stability of the catalyst powder, but also can form hydrogen bonds and other interactions with polar groups such as amino groups on the catalyst carrier, which helps to enhance the binding force between the catalyst powder and the catalyst carrier.

[0030] 3. The preparation process of the present invention does not require the use of precious metal components and high-temperature calcination equipment, which significantly reduces the complexity and cost of the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The data graph is a graph showing the content of 4-CBA in the products after hydrogenation reaction of Examples 1 to 6 and Comparative Examples 1 to 3;

[0032] Figure 2 This is a scanning electron microscope image of the product prepared in Example 1 of the present invention;

[0033] Figure 3 This is a scanning electron microscope image of the product prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0035] Example 1

[0036] 10 parts of nano-ytterbium oxide and 5 parts of potassium hydrogen oxalate were added to 40 parts of N,N-dimethylformamide, homogenized at a speed of 600 r / min for 30 min, 25 parts of acridone acetic acid were added, stirred at a speed of 500 r / min for 1 h, and then 10 parts of polyarylether nitrile were added, stirred at a speed of 500 r / min for 1 h to obtain a mixed suspension, and then heat-treated in a hot air circulation oven with a gas exhaust port at 150°C and 170°C for 12 h, respectively, and after cooling to room temperature, ethanol and deionized water were used to obtain the mixed suspension. Using water as solvent, ultrasonic treatment was carried out at a speed of 500r / min for 10 minutes, and washed with ethanol and deionized water for 3 times respectively, and then heat-treated again in a hot air circulation oven with a gas exhaust port at 220°C, 240°C and 260°C for 4 hours respectively. After cooling to room temperature, ultrasonic treatment was carried out at a speed of 500r / min for 10 minutes using ethanol and deionized water as solvent respectively, and washed with ethanol and deionized water for 3 times respectively, and finally vacuum dried at 80°C for 8 hours to obtain a catalyst carrier with a porous structure.

[0037] 20 parts of nickel copper iron magnesium powder were added to 100 parts of anhydrous ethanol, ultrasonicated at 400r / min for 20min, centrifuged at 7000rpm for 10min, and the precipitate was dried at 80°C for 2h. After cooling to room temperature, the pretreated nickel copper iron magnesium powder was obtained. 3 parts of 4-(tert-butyldimethylsilyloxy)phenylboronic acid were added to 20 parts of anhydrous ethanol, stirred at 400r / min for 30min, and then the pretreated nickel copper iron magnesium powder was added, homogenized at 400r / min for 30min, and then stirred at 400r / min for 3h at 70°C. After cooling to room temperature, it was centrifuged at 7000rpm for 10min, washed with deionized water 3 times, dried in a hot air oven at 100°C for 2h, and cooled to room temperature to obtain a catalyst powder.

[0038] 20 parts of a catalyst carrier with a porous structure were added to 100 parts of anhydrous ethanol, and homogenized at a speed of 400 r / min for 30 minutes to obtain a suspension of the catalyst carrier. 10 parts of catalyst powder were added to 50 parts of anhydrous ethanol, and homogenized at a speed of 400 r / min for 30 minutes to obtain a suspension of the catalyst powder, and then added to the suspension of the catalyst carrier at a stirring speed of 400 r / min and a drop rate of 2 mL / min. After the drop addition was completed, the reaction was continued to stir at 70°C for 4 hours, cooled to room temperature, centrifuged at 7000 rpm for 10 minutes, washed with deionized water 3 times, and then heat-treated in a hot air oven at 150°C, 200°C and 250°C for 2 hours respectively, and cooled to room temperature to obtain a terephthalic acid hydrogenation catalyst.

[0039] Example 2

[0040] 10 parts of nano-ytterbium oxide and 5 parts of potassium hydrogen oxalate were added to 40 parts of N,N-dimethylformamide, homogenized at a speed of 600 r / min for 25 min, 22 parts of acridone acetic acid were added, stirred at a speed of 400 r / min for 2 h, and then 13 parts of polyarylether nitrile were added, stirred at a speed of 400 r / min for 2 h to obtain a mixed suspension, and then heat-treated in a hot air circulation oven with a gas exhaust port at 150°C and 170°C for 12 h, respectively, and after cooling to room temperature, ethanol and deionized water were used to obtain a mixed suspension. Using water as solvent, ultrasonic treatment was carried out at a speed of 400 r / min for 10 minutes, and the mixture was washed three times with ethanol and deionized water respectively. Then, heat treatment was carried out again in a hot air circulation oven with a gas exhaust port at 220°C, 240°C and 260°C for 3 hours respectively. After cooling to room temperature, ultrasonic treatment was carried out at a speed of 400 r / min for 10 minutes with ethanol and deionized water as solvent respectively, and the mixture was washed three times with ethanol and deionized water respectively. Finally, the mixture was vacuum dried at 80°C for 9 hours to obtain a catalyst carrier with a porous structure.

[0041] 20 parts of nickel copper iron magnesium powder were added to 100 parts of anhydrous ethanol, ultrasonicated at 400r / min for 10min, centrifuged at 6000rpm for 10min, and the precipitate was dried at 80°C for 2.5h, cooled to room temperature, and the pretreated nickel copper iron magnesium powder was obtained. 3 parts of 4-(tert-butyldimethylsilyloxy)phenylboronic acid were added to 20 parts of anhydrous ethanol, stirred at 400r / min for 30min, and then the pretreated nickel copper iron magnesium powder was added, homogenized at 500r / min for 30min, and then stirred at 70°C at 300r / min for 3h, cooled to room temperature, centrifuged at 6000rpm for 12min, washed with deionized water 3 times, dried in a hot air oven at 110°C for 2.5h, and cooled to room temperature to obtain catalyst powder.

[0042] 22 parts of a catalyst carrier with a porous structure were added to 100 parts of anhydrous ethanol, and homogenized at a speed of 400 r / min for 20 minutes to obtain a suspension of the catalyst carrier. 8 parts of catalyst powder were added to 50 parts of anhydrous ethanol, and homogenized at a speed of 400 r / min for 30 minutes to obtain a suspension of the catalyst powder, and then added to the suspension of the catalyst carrier at a stirring speed of 500 r / min and a drop rate of 2 mL / min. After the drop addition was completed, the reaction was continued to stir at 60°C for 3 hours, cooled to room temperature, centrifuged at 6000 rpm for 12 minutes, washed with deionized water 3 times, and then heat-treated in a hot air oven at 150°C, 200°C and 250°C for 3 hours respectively, and cooled to room temperature to obtain a terephthalic acid hydrogenation catalyst.

[0043] Example 3

[0044] 10 parts of nano-ytterbium oxide and 5 parts of potassium hydrogen oxalate were added to 40 parts of N,N-dimethylformamide, homogenized at a speed of 700 r / min for 25 min, 23 parts of acridone acetic acid were added, stirred at a speed of 400 r / min for 1.5 h, and then 12 parts of polyarylether nitrile were added, stirred at a speed of 400 r / min for 1.5 h to obtain a mixed suspension, and then heat-treated in a hot air circulation oven with a gas exhaust port at 150°C and 170°C for 10 h, respectively, and after cooling to room temperature, ethanol and deionized water were used to obtain a mixed suspension. Deionized water was used as the solvent and ultrasonicated at a speed of 400 r / min for 15 minutes, and washed with ethanol and deionized water for 3 times respectively, and then heat-treated again in a hot air circulation oven with a gas exhaust port at 220°C, 240°C and 260°C for 3 hours respectively. After cooling to room temperature, ethanol and deionized water were used as the solvent and ultrasonicated at a speed of 400 r / min for 15 minutes respectively, and washed with ethanol and deionized water for 3 times respectively, and finally vacuum dried at 90°C for 8 hours to obtain a catalyst carrier with a porous structure.

[0045] 20 parts of nickel copper iron magnesium powder were added to 100 parts of anhydrous ethanol, ultrasonicated at 500r / min for 20min, centrifuged at 7000rpm for 13min, and the precipitate was dried at 80°C for 3h. After cooling to room temperature, the pretreated nickel copper iron magnesium powder was obtained. 3 parts of 4-(tert-butyldimethylsilyloxy)phenylboronic acid were added to 20 parts of anhydrous ethanol, stirred at 400r / min for 20min, and then the pretreated nickel copper iron magnesium powder was added, homogenized at 400r / min for 40min, and then stirred at 70°C at 400r / min for 2.5h. After cooling to room temperature, the mixture was centrifuged at 7000rpm for 13min, washed with deionized water 3 times, dried in a hot air oven at 110°C for 3h, and cooled to room temperature to obtain a catalyst powder.

[0046] 20 parts of a catalyst carrier with a porous structure were added to 100 parts of anhydrous ethanol, and homogenized at a speed of 500 r / min for 20 minutes to obtain a suspension of the catalyst carrier. 10 parts of catalyst powder were added to 50 parts of anhydrous ethanol, and homogenized at a speed of 500 r / min for 30 minutes to obtain a suspension of the catalyst powder, and then added to the suspension of the catalyst carrier at a stirring speed of 400 r / min and a drop rate of 2 mL / min. After the drop addition was completed, the reaction was continued to stir at 60°C for 3 hours, cooled to room temperature, centrifuged at 7000 rpm for 13 minutes, washed with deionized water 3 times, and then heat-treated in a hot air oven at 150°C, 200°C and 250°C for 3 hours respectively, and cooled to room temperature to obtain a terephthalic acid hydrogenation catalyst.

[0047] Example 4

[0048] 9 parts of nano-ytterbium oxide and 6 parts of potassium hydrogen oxalate were added to 45 parts of N,N-dimethylformamide, homogenized at a speed of 700 r / min for 30 min, 21 parts of acridone acetic acid were added, stirred at a speed of 500 r / min for 1.5 h, and then 14 parts of polyarylether nitrile were added, stirred at a speed of 500 r / min for 1.5 h to obtain a mixed suspension, and then heat-treated in a hot air circulation oven with a gas exhaust port at 150°C and 170°C for 10 h, respectively, and after cooling to room temperature, ethanol and deionized water were used to obtain a mixed suspension. Deionized water was used as the solvent and ultrasonicated at a speed of 500 r / min for 15 minutes, and washed with ethanol and deionized water for 3 times respectively, and then heat-treated again in a hot air circulation oven with a gas exhaust port at 220°C, 240°C and 260°C for 4 hours respectively. After cooling to room temperature, ethanol and deionized water were used as the solvent and ultrasonicated at a speed of 500 r / min for 15 minutes respectively, and washed with ethanol and deionized water for 3 times respectively, and finally vacuum dried at 90°C for 9 hours to obtain a catalyst carrier with a porous structure.

[0049] 19 parts of nickel copper iron magnesium powder were added to 100 parts of anhydrous ethanol, ultrasonicated at 500r / min for 20min, centrifuged at 6000rpm for 10min, and the precipitate was dried at 80°C for 3h. After cooling to room temperature, the pretreated nickel copper iron magnesium powder was obtained. 4 parts of 4-(tert-butyldimethylsilyloxy)phenylboronic acid were added to 20 parts of anhydrous ethanol, stirred at 400r / min for 20min, and then the pretreated nickel copper iron magnesium powder was added, homogenized at 500r / min for 30min, and then stirred at 70°C at 300r / min for 3h. After cooling to room temperature, it was centrifuged at 6000rpm for 10min, washed with deionized water 3 times, dried in a hot air oven at 100°C for 3h, and cooled to room temperature to obtain a catalyst powder.

[0050] 18 parts of a catalyst carrier with a porous structure were added to 100 parts of anhydrous ethanol, and homogenized at a speed of 500 r / min for 25 minutes to obtain a suspension of the catalyst carrier. 12 parts of catalyst powder were added to 50 parts of anhydrous ethanol, and homogenized at a speed of 500 r / min for 25 minutes to obtain a suspension of the catalyst powder, and then added to the suspension of the catalyst carrier at a stirring speed of 500 r / min and a drop rate of 2 mL / min. After the drop addition was completed, the reaction was continued to stir at 60°C for 4 hours, cooled to room temperature, centrifuged at 6000 rpm for 10 minutes, washed with deionized water 3 times, and then heat-treated in a hot air oven at 150°C, 200°C and 250°C for 2 hours respectively, and cooled to room temperature to obtain a terephthalic acid hydrogenation catalyst.

[0051] Example 5

[0052] 9 parts of nano-ytterbium oxide and 6 parts of potassium hydrogen oxalate were added to 45 parts of N,N-dimethylformamide, homogenized at 700 r / min for 20 min, 20 parts of acridone acetic acid were added, stirred at 500 r / min for 1 h, and then 15 parts of poly(arylether nitrile) were added, stirred at 500 r / min for 1 h to obtain a mixed suspension, which was then heat treated at 150°C and 170°C in a hot air circulation oven with a gas exhaust port for 11 h, respectively, and after cooling to room temperature, ethanol and deionized water were used respectively. The catalyst carrier was ultrasonically treated at 500 r / min for 10 min with ethanol and deionized water as solvent, washed 3 times with ethanol and deionized water respectively, and then heat-treated again in a hot air circulation oven with a gas exhaust port at 220°C, 240°C and 260°C for 4 h respectively. After cooling to room temperature, the catalyst carrier was ultrasonically treated at 500 r / min for 10 min with ethanol and deionized water as solvent respectively, washed 3 times with ethanol and deionized water respectively, and finally dried in vacuum at 90°C for 10 h to obtain a catalyst carrier with a porous structure.

[0053] 18 parts of nickel copper iron magnesium powder were added to 100 parts of anhydrous ethanol, ultrasonicated at 400r / min for 10 minutes, centrifuged at 7000rpm for 11 minutes, and the precipitate was dried at 80°C for 2.5 hours. After cooling to room temperature, the pretreated nickel copper iron magnesium powder was obtained. 5 parts of 4-(tert-butyldimethylsilyloxy)phenylboronic acid were added to 20 parts of anhydrous ethanol, stirred at 400r / min for 30 minutes, and then the pretreated nickel copper iron magnesium powder was added, homogenized at 400r / min for 40 minutes, and then stirred at 80°C at 400r / min for 2.5 hours. After cooling to room temperature, it was centrifuged at 7000rpm for 11 minutes, washed with deionized water 3 times, dried in a hot air oven at 100°C for 2.5 hours, and cooled to room temperature to obtain a catalyst powder.

[0054] 19 parts of a catalyst carrier with a porous structure were added to 100 parts of anhydrous ethanol, and homogenized at a speed of 400 r / min for 30 minutes to obtain a suspension of the catalyst carrier. 11 parts of catalyst powder were added to 50 parts of anhydrous ethanol, and homogenized at a speed of 400 r / min for 30 minutes to obtain a suspension of the catalyst powder, and then added to the suspension of the catalyst carrier at a stirring speed of 400 r / min and a drop rate of 2 mL / min. After the drop addition was completed, the reaction was continued to stir at 70°C for 3.5 hours, cooled to room temperature, centrifuged at 7000 rpm for 11 minutes, washed with deionized water 3 times, and then heat treated in a hot air oven at 150°C, 200°C and 250°C for 2.5 hours respectively, and cooled to room temperature to obtain a terephthalic acid hydrogenation catalyst.

[0055] Example 6

[0056] 8 parts of nano-ytterbium oxide and 7 parts of potassium hydrogen oxalate were added to 50 parts of N,N-dimethylformamide, homogenized at a speed of 600 r / min for 30 min, 18 parts of acridone acetic acid were added, stirred at a speed of 400 r / min for 1.5 h, and then 7 parts of polyarylether nitrile were added, stirred at a speed of 400 r / min for 1.5 h to obtain a mixed suspension, and then heat-treated in a hot air circulation oven with a gas exhaust port at 150°C and 170°C for 11 h, respectively, and after cooling to room temperature, ethanol and deionized water were used to obtain the mixed suspension. The mixture was ultrasonically treated at a speed of 400 r / min for 10 minutes using deionized water as solvent, and washed three times with ethanol and deionized water respectively, and then heat-treated again in a hot air circulation oven with a gas exhaust port at 220°C, 240°C and 260°C for 3 hours respectively. After cooling to room temperature, the mixture was ultrasonically treated at a speed of 400 r / min for 10 minutes using ethanol and deionized water as solvent respectively, and washed three times with ethanol and deionized water respectively, and finally vacuum dried at 80°C for 10 hours to obtain a catalyst carrier with a porous structure.

[0057] 18 parts of nickel copper iron magnesium powder were added to 100 parts of anhydrous ethanol, ultrasonicated at 500r / min for 10min, centrifuged at 7000rpm for 15min, and the precipitate was dried at 80°C for 2.5h, cooled to room temperature, and the pretreated nickel copper iron magnesium powder was obtained. 5 parts of 4-(tert-butyldimethylsilyloxy)phenylboronic acid were added to 20 parts of anhydrous ethanol, stirred at 500r / min for 30min, and then the pretreated nickel copper iron magnesium powder was added, homogenized at 500r / min for 30min, and then stirred at 80°C at 300r / min for 2.5h, cooled to room temperature, centrifuged at 7000rpm for 15min, washed with deionized water 3 times, dried in a hot air oven at 110°C for 2.5h, and cooled to room temperature to obtain catalyst powder.

[0058] 20 parts of a catalyst carrier with a porous structure were added to 100 parts of anhydrous ethanol, homogenized at a speed of 400 r / min for 25 minutes to obtain a suspension of the catalyst carrier. 10 parts of catalyst powder were added to 50 parts of anhydrous ethanol, homogenized at a speed of 400 r / min for 25 minutes to obtain a suspension of the catalyst powder, and then added to the suspension of the catalyst carrier at a stirring speed of 500 r / min and a drop rate of 2 mL / min. After the drop addition was completed, the reaction was continued to stir at 70°C for 3.5 hours, cooled to room temperature, centrifuged at 7000 rpm for 15 minutes, washed with deionized water 3 times, and then heat treated in a hot air oven at 150°C, 200°C and 250°C for 2.5 hours respectively, and cooled to room temperature to obtain a terephthalic acid hydrogenation catalyst.

[0059] The present invention also provides comparative examples and related tests.

[0060] Comparative Example 1

[0061] The difference between Comparative Example 1 and Example 1 is that, during the preparation of the catalyst carrier, potassium hydrogen oxalate was not added, and subsequent treatments such as step-by-step heat treatment and curing were directly carried out. The other compositions and preparation methods were the same as those of Example 1, and a terephthalic acid hydrogenation catalyst was finally prepared.

[0062] Comparative Example 2

[0063] The difference between Comparative Example 2 and Example 1 is that no catalyst powder is prepared, and 20 parts of commercially available nickel-copper-iron-magnesium powder is directly used to replace 20 parts of catalyst powder. The other compositions and preparation methods are the same as those of Example 1, and finally a terephthalic acid hydrogenation catalyst is prepared.

[0064] Comparative Example 3

[0065] The difference between Comparative Example 3 and Example 1 is that the catalyst carrier is not prepared, and 50 parts of commercially available activated carbon are directly used to replace 50 parts of the catalyst carrier. The other compositions and preparation methods are the same as those of Example 1, and finally a terephthalic acid hydrogenation catalyst is prepared.

[0066] Performance testing test.

[0067] In 9 1L reactors, 5 parts of the terephthalic acid hydrogenation catalyst prepared in the above Examples 1 to 6 and Comparative Examples 1 to 3 were added respectively, and then 15 parts of terephthalic acid, 1 part of p-carboxybenzaldehyde and 600 parts of water were added to each reactor. All were placed in the same environment, at a reaction temperature of 260° C. and a hydrogen pressure of 0.6 MPa, and the reaction was carried out for 2 hours. After filtering out the water, the 4-CBA content was tested in accordance with GB / T30921.1-2014. The test data are shown in Table 1. The content data of 4-CBA in the products after the hydrogenation reaction of Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 1. Figure 1 shown.

[0068] The terephthalic acid hydrogenation catalysts prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were tested for specific surface area, particle size, and compressive strength according to GB / T19587-2017, GB / T19077-2016, and GB / T43091-2023, respectively. The test data are shown in Table 1.

[0069] Table 1

[0070]

[0071] As shown in Table 1, the test results of the terephthalic acid hydrogenation catalysts prepared in Examples 1 to 6 are significantly better than those prepared in Comparative Examples 1 to 3, and Example 1 has the best performance, which is the best solution of the present invention. The products prepared in Examples 1 and 2 were tested by scanning electron microscopy, and the results are as follows: Figure 2 , 3 shown.

[0072] By comparing the specific surface area, particle size, and compressive strength test data of Examples 1 to 6 with those of Comparative Examples 1 to 3, it can be seen that when potassium hydrogen oxalate is not added during the preparation of the catalyst carrier, and subsequent treatments such as step-by-step heat treatment and curing are directly performed, the specific surface area, particle size, and compressive strength are significantly smaller than those of Examples 1 to 6, among which the specific surface area is the smallest, which is only 139 m 2 / g, indicating that without the addition of potassium hydrogen oxalate, the carrier cannot form a porous structure, resulting in a smaller specific surface area of ​​the prepared hydrogenation catalyst, and cannot load more catalyst powder, thus affecting the catalytic performance; when commercially available nickel-copper-iron-magnesium powder is used to replace the catalyst powder, the binding force between the commercially available nickel-copper-iron-magnesium powder and the catalyst carrier is relatively smaller than that of the catalyst powder, resulting in less commercially available nickel-copper-iron-magnesium powder loaded on the catalyst carrier, resulting in a smaller particle size of the prepared hydrogenation catalyst, and its specific surface area and compressive strength are slightly reduced; when commercially available activated carbon is used to replace the catalyst carrier, its specific surface area and particle size are slightly reduced, and the compressive strength is the smallest, only 9MPa. It can be seen that the change of the catalyst carrier has a greater impact on the compressive strength of the hydrogenation catalyst.

[0073] Comparison of the test data of 4-CBA content in the products after hydrogenation reaction of the catalysts prepared by Example 1 and Comparative Examples 1 to 3 in Table 1 Figure 1 The data graph of the content of 4-CBA in the products after the hydrogenation reaction of Examples 1 to 6 and Comparative Examples 1 to 3 shows that the contents of 4-CBA in Comparative Examples 1 to 3 are 179 ppmw, 217 ppmw and 154 ppmw, respectively, which are all higher than 5 ppmw in Example 1. It can be seen that when commercially available nickel-copper-iron-magnesium powder is used to replace the catalyst powder to prepare the hydrogenation catalyst and carry out the hydrogenation reaction, the content of 4-CBA remaining in the product is the highest, indicating that the catalytic effect of the hydrogenation catalyst prepared by the comparative example is the worst, that is, the replacement of the catalyst powder has the greatest impact on the catalytic effect; and when potassium hydrogen oxalate is not added in the preparation process of the catalyst carrier, and commercially available activated carbon is used to replace the catalyst carrier to prepare the hydrogenation catalyst and carry out the hydrogenation reaction, the content of 4-CBA remaining in the product is high, but less than that of Comparative Example 2, indicating that the hydrogenation catalysts prepared by Comparative Examples 1 and 3 have a certain effect on the hydrogenation catalytic effect, but not as great as the effect brought by replacing the catalyst powder.

[0074] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a terephthalic acid hydrogenation catalyst, characterized in that: The following steps are involved: S1, mixing nano-ytterbium oxide, potassium hydrogen oxalate, acridone acetic acid and poly(arylene ether nitrile) to obtain a mixed suspension, then heat-treating, cooling, ultrasonicating and washing, and heat-treating, cooling, ultrasonicating and washing again, and after drying and cooling, obtaining a catalyst carrier with a porous structure; S2, adding 4-(tert-butyldimethylsilyloxy)phenylboric acid to ethanol, stirring, adding pretreated nickel, copper, iron and magnesium powders, homogenizing, heating and stirring, cooling, centrifuging, washing and drying to obtain catalyst powder; S3. Add the suspension of catalyst powder into the suspension of catalyst carrier, heat and stir, cool, centrifuge, wash, heat treat and cool to obtain terephthalic acid hydrogenation catalyst.

2. The method for preparing a terephthalic acid hydrogenation catalyst according to claim 1, characterized in that: In the step S1, nano-ytterbium oxide and potassium hydrogen oxalate are added to N,N-dimethylformamide, homogenized at 600-700 r / min for 20-30 min, acridone acetic acid is added, stirred at 400-500 r / min for 1-2 h, and then polyarylether nitrile is added, stirred at 400-500 r / min for 1-2 h to obtain a mixed suspension.

3. The method for preparing a terephthalic acid hydrogenation catalyst according to claim 1, characterized in that: In the step S1, the catalyst carrier with a porous structure is heat-treated in a hot air circulation oven with a gas exhaust port at 150°C and 170°C for 10-12 hours respectively, cooled to room temperature, ultrasonicated at a speed of 400-500 r / min for 10-15 minutes, washed, and then heat-treated again in a hot air circulation oven with a gas exhaust port at 220°C, 240°C and 260°C for 3-4 hours respectively, cooled to room temperature, ultrasonicated at a speed of 400-500 r / min for 10-15 minutes, washed, dried at 80-90°C for 8-10 hours, and cooled to room temperature to obtain.

4. The method for preparing a terephthalic acid hydrogenation catalyst according to claim 1, characterized in that: In the step S2, the pretreated nickel-copper-iron-magnesium powder is obtained by ultrasonicating the nickel-copper-iron-magnesium powder in anhydrous ethanol at a speed of 400-500 r / min for 10-20 min, centrifuging at 6000-7000 rpm for 10-15 min, drying the precipitate at 80-90° C. for 2-3 h, and cooling it to room temperature.

5. The method for preparing a terephthalic acid hydrogenation catalyst according to claim 1, characterized in that: In the step S2, 4-(tert-butyldimethylsilyloxy)phenylboronic acid is added to ethanol, and the mixture is stirred at a speed of 400-500 r / min for 20-30 min, and then the pretreated nickel-copper-iron-magnesium powder is added, and the mixture is homogenized at a speed of 400-500 r / min for 30-40 min, and then stirred at a speed of 300-400 r / min for 2-3 h at 70-80 ° C., cooled to room temperature, centrifuged at 6000-7000 rpm for 10-15 min, washed, dried in a hot air oven at 100-110 ° C. for 2-3 h, and cooled to room temperature to obtain a catalyst powder.

6. The method for preparing a terephthalic acid hydrogenation catalyst according to claim 5, characterized in that: In the step S2, the mass ratio of the pretreated nickel-copper-iron-magnesium powder to 4-(tert-butyldimethylsilyloxy)phenylboric acid is 20:

3.

7. The method for preparing a terephthalic acid hydrogenation catalyst according to claim 1, characterized in that: In the step S3, the catalyst powder suspension is obtained by homogenizing the catalyst powder in ethanol at 400-500 r / min for 20-30 min; the catalyst carrier suspension is obtained by homogenizing the catalyst carrier in ethanol at 400-500 r / min for 20-30 min.

8. The method for preparing a terephthalic acid hydrogenation catalyst according to claim 1, characterized in that: In the step S3, the terephthalic acid hydrogenation catalyst is prepared by adding a suspension of catalyst powder to a suspension of a catalyst carrier at a stirring speed of 400 r / min and a dropping speed of 2 mL / min, and after the dropping is completed, stirring and reacting at 60-70° C. for 3-4 hours, cooling to room temperature, centrifuging at 6000-7000 rpm for 10-15 minutes, washing, and then heat-treating in a hot air oven at 150° C., 200° C. and 250° C. for 2-3 hours respectively, and cooling to room temperature to obtain.

9. A terephthalic acid hydrogenation catalyst, characterized in that: The catalyst is prepared by the method for preparing a terephthalic acid hydrogenation catalyst according to any one of claims 1 to 8, and comprises the following raw materials in parts by weight: 10 to 12 parts of nano ytterbium oxide, 25 to 30 parts of acridone acetic acid, 5 to 6 parts of potassium hydrogen oxalate, 8 to 10 parts of polyarylether nitrile, 20 to 25 parts of nickel copper iron magnesium powder, 3 to 3.5 parts of 4-(tert-butyldimethylsilyloxy)phenylboric acid, and 40 to 50 parts of N,N-dimethylformamide.

10. An application of a hydrogenation catalyst, characterized in that: The terephthalic acid hydrogenation catalyst described in claim 9 is used to carry out a hydrogenation catalytic reaction on p-carboxybenzaldehyde contained in crude terephthalic acid to produce p-toluic acid.

Citation Information

Patent Citations

  • Hydrofining reaction and catalyst thereof

    CN112239404A

  • Gas phase heterogeneous catalytic oxidation of alkanes to aliphatic ketones and / or other oxygenates

    CN103596909A

  • Preparation method of hydrogenation catalyst

    CN106140208A